STRATEGI PERENCANAAN PENGEMBANGAN SEKOLAH ALAM TUNAS MULIA UNTUK KESEJAHTERAAN EKONOMI MASYARAKAT DI BANTAR GEBANG – BEKASI - Teguh Santosa (Develop: Jurnal Ekonomi Pembangunan, 2021)
This study aims to determine the planning strategy for the development of the natural school development of the Tunas Mulia Bantar Gebang school for the economic welfare of the community. The method used in the research is qualitative with a descriptive approach, this research was conducted from February 15th to March 29th, 2021, with the subjects of Tunas Alam Mulia School students and with a sample of 30 students' parents, the data collection techniques in this research were interviews, observation, and documentation. Based on the SWOT analysis above, the main strategy is an Integrative Strategy, this shows that in the Yayasan Tunas Mulia, it must carry out its activities by integrating weaknesses and opportunities in order to overcome weaknesses by taking advantage of opportunities at the Yayasan Tunas Mulia.